Effects of the Anger Management Program for Nurses - Kyoungsun Yun; Yang-Sook Yoo (Elsevier, 2021)
ABSTRACT: Purpose: The purpose of this study was to examine the effects of an anger management program on anger, job stress, psychological well-being, and heart rate variability in clinical nurses. Methods: A quasi-experimental study was conducted using a nonequivalent control group, pre-post test design with repeated measures. The participants included 43 nurses assigned to the experimental and control groups. Anger, job stress, psychological well-being, and heart rate variability were evaluated before the intervention, immediately after the completion of the intervention, and four weeks after the end of the intervention. Chi-square test, t-test, Fisher's exact test, and GEE (Generalized Estimating Equations) were used to analyze the data. Results: There were significant differences in the level of anger, state anger, job stress, and psychological well-being between the two groups. The rate of change in the total power (TP) and the high-frequency band (HF) of the experimental group increased immediately after the intervention completion, but that of the control group decreased at the same time. Conclusion: The above results demonstrate that an anger management program for nurses effectively attenuated anger and job stress, improved psychological well-being, and regulated heart rate variability.